Surprising magic of CD24 beyond cancer - Wang, He; Shi, Peng; Shi, Xinyu; Lv, Yaqing; Xie, Hongwei; Zhao, Hai (Frontiers in Immunology, 2024)
CD24 has emerged as a molecule of significant interest beyond the oncological arena.Recent studies have unveiled its surprising and diverse roles in various biological processes and diseases. This review encapsulates the expanding spectrum of CD24 functions, delving into its involvement in immune regulation, cancer immune microenvironment, and its potential as a therapeutic target in autoimmune diseases and beyond. The 'magic' of CD24, once solely attributed to cancer, now inspires a new paradigm in understanding its multifunctionality in human health and disease, offering exciting prospects for medical advancements.